Prosedur Teknik Pemeriksaan Magnetic Resonance Spectroscopy Pada Kasus Tumor Otak Di Instalasi Radiologi RS Pusat Pertamina Jakarta - Saybivo Chandra; Ni Putu Rita Jeniyanti; Tri Asih Budiati (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Procedure For Magnetic Resonance Spectroscopy Examination Technique In Brain Tumor Cases At The Radiology Installation Of Pertamina Central Hospital Jakarta. MR spectroscopy is one way of describing metabolites in tumor tissue without being invasive. Single spectroscopic approach, which is used in Magnetic Resonance Spectroscopy and is the most common spectral collection method in MRI modalities. MRi is the establishment of a medical diagnosis based on the principle of magnetic resonance. MRI aircraft produce images in various pieces namely coronal, sagittal, and transverse by not at all using x-rays that produce radiation and also using radioactive substances. Brain tumors are abnormally growing brain tissue cells originating from the brain or meningens, which are benign or malignant tumors that make massive pressure. MRS is a unique non-invasive sequence that helps in the identification of lesion molecules and the difference between malignant and benign lesions. In MRI examination of the brain with tumor cases there are several sequences used, namely Se / Fse Pd / T2, Se / Fse / incoherent spoiled, (DWI) diffusion weighted imaging (1) According to Elmaoglu (2), imaging techniques that can be used for MRI brain tumor cases include axial T1 spin echo, T2 fast recovery fast spin echo, T2 FLAIR, coronal T1 and T1 Axial post contrast injection, T1 coronal, and T1 sagittal, diffusion weighted imaging (DWI), magnetic resonance angiography, and magnetic resonance spectroscopy. In taking SVS LESION localizer must be precise on tumor tissue not taking part that is not part of the tumor, analyze tumor area and take SVS NORMAL localizer on other healthy tissue.